Tagatose as a Potential Nutraceutical: Production, Properties, Biological Roles, and Applications. Issue 11 (18th October 2018) - Roy, Sohini; Chikkerur, Jayaram; Roy, Sudhir Chandra; Dhali, Arindam; Kolte, Atul Puroshtam; Sridhar, Manpal; Samanta, Ashis Kumar
Abstract: Nutraceuticals are gaining importance owing to their potential applications in numerous sectors including food and feed industries. Among the emerging nutraceuticals, d ‐tagatose occupies a significant niche because of its low calorific value, antidiabetic property and growth promoting effects on beneficial gut bacteria. Asd ‐tagatose is present in minute quantities in naturally occurring food substances, it is produced mainly by chemical or biological means. Recently, attempts were made for bio‐production ofd ‐tagatose usingl ‐arabinose isomerase enzyme to overcome the challenges of chemical process of production. Applications ofd ‐tagatose for maintaining health and wellbeing are increasing due to growing consumer awareness and apprehension against modern therapeutic agents. This review outlines the current status ond ‐tagatose, particularly its production, properties, biological role, applications, and the future perspectives.